Efektivitas Pengunaan Simulasi PhET dalam Meningkatkan Pemahaman Mahasiswa pada Efek Compton - Sinaga, Cindy E.; Monika, Febi; Salz, Noor Putri; Zukhairia, Siti (IAI Nasional Laa Roiba Bogor, 2025)
This study aims to explore the effect of using PhET simulations in improving students' understanding of the Compton Effect concept. The research design employed was a quasi-experimental One-Group Pretest-Posttest Design, involving five students as the research sample. Data were collected through pretest and posttest assessments, along with questionnaires to gather students' responses to the learning experience. The results showed a significant improvement in students' understanding after using the PhET simulation. The average pretest score was 32, which increased to 80 in the posttest. Statistical analysis using paired sample t-test indicated a significant difference between pretest and posttest (p<0.05). Students reported that the PhET simulation helped them understand difficult physics concepts more effectively than conventional methods. Overall, the PhET simulation proved to be effective in enhancing students' understanding of the Compton Effect and can serve as a valuable alternative in higher education learning.